Pengaruh Berbagai Waktu Pemotongan Pucuk Bahan Setek dan Taraf Dosis Rootone F Terhadap Pertumbuhan Setek Pendek Panili (Vanilla Planifolia Andrews) - TAMPUBOLON, VITARIVERA; SUTEJA, I NYOMAN; DHARMA, I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.1, Januari 2016, 2016)
ABSTRACT Effect of Various Timing on Bud Cutting as Cuttings Material and Dosage of Rootone F on the Growth of Vanilla Short-Cutting ( V anilla planifolia Andrews) Vanilla (Vanilla planifolia Andrews) can generally be propagated by seed (generative) and vegetative by cuttings. As the multiplication by seed takes longer to flowering, thus the vanilla propagation for commercial purpose is done by cuttings. This study aims to determine the effect of time on bud cutting as cuttings material and dosage of Rootone F as well as its interactions on the growth of vanilla short-cuttings. This study uses two factors factorial design, i.e.: time on bud cutting as cuttings material and dosage of Rootone F. The result of the research showed an interaction between time on bud cutting as cuttings material and dosage of Rootone F provides a very significant effect on the variable of oven dried stems shoots weight, and showed a significant effect on the variable total oven dry weight; while other variables showed no significant effect. Treatment of time on bud cutting as cuttings material (P) showed highly significant effect on the variable of time to sprout, while the other variables showed no significant effect. Dosage of Rootone F (D) showed no significant effect on all variables. The interaction of time on bud cutting as cuttings material 8 days before planting with Rootone F dose of 100 mg / 1 ml of water provides a better growth of vanilla short-cuttings with the highest total oven dry weight is 1,12 grams and has increased 89.83% compared to the bud cut when the cuttings is about to be planted and Rootone F dose of 0 mg / 0 ml of water. Keywords: V anilla time on shoot-cutting as cuttings material, Rootone F, nurseries, vanilla.